ICT in Language Learning: Benefits and Methodological Implications - Jumayeva Nilufar Xudoyor qizi (Zeta Repository, 2023)
ICT as a teaching medium is gaining popularity. In this post, we want to offer some aspects of using ICT that have benefited and stimulated both students and teachers. We discuss our experiences using the Blackboard e-learning environment for teaching language classes in English and Swedish (at various levels), learning terminology, and ESP (English for Specific Purposes). Our focus will be on how the web-based environment may facilitate student-centered learning by improving student motivation, individualization, and cooperation in creating study materials while developing a sense of "us" and belonging. Looking at our past and current courses, we will see how we may motivate students by including them in creating learning resources such as databases on specialized study themes, PowerPoint presentations, and online dictionaries. We examine how ICT solutions can be used to support various classroom activities, group work, and pair work assignments; for independent work; for enforcing student-centered learning and individualization principles; and for forming one’s personal opinion and being able to express it on current issues.